Nano Carbon/Vertical Graphene/MnO2 Nanosheets Composite Particles for High‐Performance Supercapacitors. Issue 3 (8th January 2022) - Li, Shiwen; Lin, Junsheng; Zhao, Lei; Ren, Zhonghua; Yu, Jie
Abstract : Compounding carbon substrate materials with pseudocapacitive materials is an important strategy for making high‐performance supercapacitor materials. Nano carbon black (CB) is widely used as the conductive additive in energy storage devices owing to its low cost, high conductivity, good spreadability, and excellent ability of adsorbing electrolyte, reducing the binder consumption, adjusting the pore size and fraction of the electrode, and high‐voltage operation. However, very little attention has been paid to applying CB as the substrate materials for producing composite active materials. Herein, a surface‐modified CB is developed by growing vertical graphene nanosheets on the surface of CB by chemical vapor deposition. After growing MnO2 nanosheets on the modified CB, the obtained nanocomposites deliver high specific capacitance, rate performance, and cycling stability. The assembled symmetric supercapacitor obtains a high energy density of 54 Wh kg −1 at a power density of 181 W kg −1 . Systematic experimental research reveals the superior performance benefits from the surface modification of CB by vertical graphene nanosheets, which improves the electrical conductivity, thermal stability, and pore structure of the whole electrodes. This method is of great promise for the development of new materials for high‐performance supercapacitors. Abstract : A nano carbon/vertical graphene/MnO2 nanosheets composite nanoparticle is developed by growing MnO2 nanosheets on a surface‐modified nano carbon black (CB) by vertically aligned graphene nanosheets. The obtained nanocomposites and assembled supercapacitors deliver superior electrochemical performance, benefiting from the improved electrical conductivity, thermal stability, and pore structure of the electrodes by the vertical graphene nanosheets.